An easy methodology for frost tolerance assessment in olive cultivars - Valverde, Pedro; Lodolini, Enrico Maria; Giorgi, Veronica; Garcia-Lopez, Maria Teresa; Neri, Davide (Frontiers in Plant Science, 2024)
Introduction Olive cultivation, like other evergreen fruit crops worldwide, is limited by the occurrence of frost episodes in different times of the year, mainly in winter or early spring. Some contradictory results are reported about cultivars’ response to frost, which depends on the physiological stage of the tissues (acclimated or not acclimated) when the cold or frost episode occurs. This work aimed to implement a user-friendly and reliable lab method for discerning frost tolerance. Methods Our methodology considered both detached leaves and potted plantlets. The optimal temperature at which damage differentiated between cultivars was evaluated, as well as the time of exposure to cold and the recovery time for the correct evaluation of the symptoms. Furthermore, a comparative analysis of damage on both young and mature leaves was conducted. To validate the efficacy of the methodology, assessments were conducted on the cultivars ‘Arbequina’ (tolerant), ‘Picual’ (moderately tolerant), and ‘Frantoio’ (susceptible) under acclimated and non-acclimated conditions. Results and discussion The results indicated that, when detached leaves were used for frost evaluation, a temperature of -10°C ± 1°C for 30 min and a recovery time at 26°C for 24–48 h after exposure to cold are enough to induce damages on the leaves and discriminate between cultivar susceptibility. Under these conditions, a precise assessment of symptoms can be made, facilitating the categorization of frost tolerance level in various olive cultivars. Notably, no significant differences were observed between young and mature leaves during the evaluation process. On the other hand, the critical temperature to assess damages on potted plantlets was determined to be -7°C ± 1°C. In addition, it was observed that acclimated plants exhibited fewer symptoms compared to non-acclimated ones, with ‘Frantoio’ being the most affected alongside ‘Picual’ and ‘Arbequina’. Conclusion The implemented methodology will allow the assessment of frost tolerance in several olive cultivars within a short timeframe, and it is proven to be user-friendly and reliable.